2020
DOI: 10.1148/radiol.2020200032
|View full text |Cite
|
Sign up to set email alerts
|

Improved Sensitivity and Reader Confidence in CT Colonography Using Dual-Layer Spectral CT: A Phantom Study

Abstract: Background: Limited cathartic preparations for CT colonography with fecal tagging can improve patient comfort but may result in nondiagnostic examinations from poorly tagged stool. Dual-energy CT may overcome this limitation by improving the conspicuity of the contrast agent, but more data are needed.Purpose: To investigate whether dual-energy CT improves polyp detection in CT colonography compared with conventional CT at different fecal tagging levels in vitro. Materials and Methods:In this HIPAA-compliant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previous studies of DECT have focused on high energy VMI to reduce metal artifact, since low energy VMI increase artifact. However, in abdominal imaging mostly low energy VMIs are employed to investigate clinical questions: Improve vascular contrast and create arterial phase-like images from venous phase images [ 33 ], increase conspicuity of pancreatic or hepatic lesions [ 34 ], bowel wall ischemia [ 35 , 36 ], or sensitivity in CT colonography [ 37 ]. Using iMAR may be a way to enable the use of low keV VMI with metal implants.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of DECT have focused on high energy VMI to reduce metal artifact, since low energy VMI increase artifact. However, in abdominal imaging mostly low energy VMIs are employed to investigate clinical questions: Improve vascular contrast and create arterial phase-like images from venous phase images [ 33 ], increase conspicuity of pancreatic or hepatic lesions [ 34 ], bowel wall ischemia [ 35 , 36 ], or sensitivity in CT colonography [ 37 ]. Using iMAR may be a way to enable the use of low keV VMI with metal implants.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent investigation further strengthened these promising results. The authors found that 40-keV monoenergetic images showed higher overall sensitivity in polyp detection compared with conventional 120 kVp PEI (58.8% vs. 42.1%, p < 0.001) and improved reader confidence at different fecal tagging levels (p < 0.001) in a colon phantom [56].…”
Section: Gastrointestinal Tractmentioning
confidence: 97%
“…As DECT technology continues to evolve, multiple new technical innovations are anticipated to improve the value of multi-energy CT for evaluation of the gastrointestinal tract. Currently, groups are embracing the high sensitivity and quantitative nature of DECT to define useful thresholds for diagnoses, to expand its clinical applications [e.g., perfusion DECT for tumor characterization and treatment monitoring [76]; liver fibrosis [77]; DECT augmentation of suboptimal stool tagging during CT colonography [78] (Figure 10)], and to further reduce radiation and contrast dose for all CT imaging [63].…”
Section: Future Applicationsmentioning
confidence: 99%